Medicinal and aromatic plants farming Prospective intervention for fluorosis in livestock - Shaurya, Shruti; Kumari, Rashmi Rekha; Kumar, Pankaj; Das, Anup (Indian Farming, 2024)
Fluorosis is a debilitating condition caused by excessive fluoride intake in food and water. It is a pervasive health issue in India, particularly in regions where fluoride levels in water and soil exceed safe limits of 1.5 mg/L. This condition affects millions of humans and livestock, leading to severe dental and skeletal deformities that compromise animal health, reduce productivity, and cause significant economic losses for farmers. The livestock population in endemic regions (Rajasthan, Andhra Pradesh, Bihar, Gujarat, Punjab etc.) of India is at risk. The cultivation of MAPs not only offers a natural remedy for managing fluorosis in livestock but also presents a viable economic opportunity for Indian farmers. As the global demand for organic products and natural remedies grows, integrating MAPs into Indian farming systems can increase farm income while improving livestock health. This dual benefit makes MAPs a sustainable and economically advantageous solution to the fluorosis problem.